Ethical Conduct in Health Services in Turkey - ÇEKİN, MURAT DİNÇER (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2012)
The survey aims to explore the attitudes of physicians, nurses, pharmacists, pharmaceutical representatives, and patients from two provinces of Turkey, Nevsehir and Istanbul, in context of ethical conduct within the health services and the relation between the health services and its suppliers, particularly the pharmaceutical industry. Quantitative and qualitative methods were used together. The questionnaire interviews were conveyed to a total of 1540 people and eight focus group discussions to 85 people during April-May 2009. The most common unethical acts in medical practice are knife payment/additional informal payment, self-referral, patient discrimination, discrediting other physicians, unnecessary tests-interventions-prescriptions, accepting promotion and demand for personal-household goods, preferring products that come along with promotion, getting cash per box, sponsored vacations in the form of medical congress. Eliminating monetary relationship between the physician and the patient; discouraging close contact of the physician and the healthcare institution with the pharmaceutical industry; implementing commissions in hospitals to supervise physicians for preventing patient discrimination and unnecessary interventions within the framework of good clinical practices; building a supreme board of medical journalism to prevent artificial demand for medical interventions and creation of false hopes, are the proposed precautions for corruption in health services.